Sedimentation of silver and palladium on the silicon surface by galvanic replacement - Shepida, Maryana; Dobrovetska, Oksana (Видавництво Львівської політехніки, 2017)
The results of investigations of the process of precipitation of micro- and nanosized particles of silver and palladium on the surface of silicon by electroplating substitution are presented. The conditions of the process, in which a nanosized precipitate is formed in the environment of organic aprotic solvents, is established. The influence of the concentration of metal ions in the solution, temperature and duration of galvanic substitution on the morphology of the modified surface, the geometry of the sediment particles and their distribution in size have been studied.
Keywords: galvanic replacement; nanoparticles; silver; palladium; silicon surface; aprotic solvents